Optimalisasi Performa Lompat Tinggi: Pengaruh Daya Tungkai dan Fleksibilitas Pinggul dalam Teknik Fosbury Flop - M. Arie Desman; Alnedral Alnedral; Arsil Arsil; Muhammad Fakhrur Rozi; Juanda Putra; Jeki Haryanto (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
The purpose of this study was to determine the contribution of lower limb explosive power and waist flexibility to the performance of the flop-style high jump among students in the Department of Coaching Education, Faculty of Sports Science, Universitas Negeri Padang (FIK-UNP). This research was motivated by the observed low performance in the high jump, which is suspected to be influenced by insufficient explosive leg power and limited flexibility in the waist area. This study employed a correlational research design. The population consisted of 39 students enrolled in an advanced athletics course, comprising 37 male and 6 female students. A total of 37 participants were selected using purposive sampling. The instruments used were: the vertical jump test (using the Lewis formula) to measure lower limb explosive power, the bridge-up test to assess waist flexibility, and a standardized flop-style high jump test to evaluate high jump performance. Data were analyzed using single and multiple correlation techniques, followed by the calculation of the coefficient of determination (R² × 100%) to identify the contribution of each independent variable. The results showed that: (1) lower limb explosive power contributed 61.62% to high jump performance; (2) waist flexibility contributed 30.91%; and (3) both variables together contributed 69.22% to the students' flop-style high jump performance.